Primary Acinic Cell Carcinoma of the Breast: A Case Report and Review of the Literature. (April 2014) - Zhao, Yang; Li, Weidong; Lang, Ronggang; Yang, Yiling; Gao, Xia; Zheng, Yi; Zhang, Chao; Fu, Xilin; Fu, Li
Acinic cell carcinoma (ACC) of the breast is a rare tumor that is listed in the 2003 World Health Organization (WHO) classification of tumors of the breast. Pure form ACC of the breast is even rarer. To date, only 12 cases have been reported in the English-language literature. A case of primary ACC of the breast in a 38-year-old woman is presented in this report. Histologically, the neoplastic cells are characterized by widespread acinci cell-like differentiation with a eosinophilic granular or clear cytoplasm, resembling acinic cells of the parotid gland. In addition, the neoplastic cells are positive for lysozyme, EMA, S-100, CD68 and GCDFP-15 and negative for α-anti-chymotrypsin, synaptophysin, ER, PR and Her-2/neu. This primary breast tumor was confirmed by clinical, morphological, and immunohistochemical studies. Characteristic features and differential diagnosis of this tumor were discussed in the light of pertinent literature.